ANALISIS EFISIENSI BIAYA OPERASIONAL TERHADAP PERTUMBUHAN LABA BERSIH PADA PT. SIDOMUNCUL TBK - Dewi, Sukma; Puji Muniarty (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to analyze the effect of operating cost efficiency on net profit growth at PT Industri Jamu dan Farmasi Sido Muncul Tbk. Operating cost efficiency is an important indicator in assessing management's ability to allocate resources optimally to support company profitability. The background of this research is based on the dynamics of the pharmaceutical and herbal industry sector in Indonesia as well as fluctuations in raw material prices and distribution costs that affect the company's financial performance. The research method used is quantitative with a causal associative approach. The data used is secondary data in the form of annual financial reports for the 2020–2025 period obtained from the Indonesia Stock Exchange. The sampling technique was carried out using purposive sampling, and data analysis was performed through descriptive analysis and associative analysis using the Operating Expense Ratio (OER/BOPO). The results showed that operating cost efficiency has a negative and significant effect on net profit growth. These findings indicate that the lower the BOPO ratio (the more efficient), the higher the company's net profit growth tends to be. Empirical evidence shows that in 2022 when the BOPO ratio increased to 65%, net profit growth experienced a negative contraction of -15.22%. Conversely, when the company succeeded in reducing and maintaining the BOPO ratio at 60% through a marketing digitalization strategy in the 2023–2025 period, net profit growth returned to positive at 34.62%, 19.05%, and 10.40%, respectively. This study concludes that disciplined control of operating costs is a key determinant of company profitability. The managerial implication of this research is the need for the company to consistently maintain operating cost discipline and periodically evaluate the effectiveness of each cost item to maintain net profit growth amidst future fluctuations in raw material prices in the pharmaceutical industry.